2017
DOI: 10.18483/ijsci.1225
|View full text |Cite
|
Sign up to set email alerts
|

A New Inhibitor of γ-aminobutric Acid Aminotransferase from Streptomyces sp. ZZ035 Isolated from a Folk Medicinal Soil in China

Abstract: Strain ZZ035 was isolated from a folk medicinal soil in China. Polyphasic taxonomy procedure indicated that this strain belonged to the genus Streptomyces and was closest to S. cinnamonensis with high similarities (99.2%) of 16S rDNA sequence. 1 was isolated from the broth of this strain and identified as 5-amonimethyl-2-iminoimidazolidine-4-carboxylic acid. Its chemical structure was established by its spectroscopic data, and 1 H and 13 C signals were assigned by its 1 H, 13C, Dept and HSQC spectra. Consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Polyphasic taxonomy procedure indicated that this strain belonged to the genus Streptomyces and was closest to S. cinnamonensis [2]. Its 16S deoxyribonucleic acid (16S rDNA) sequence was deposited at NCBI GenBank with accession numbers KJ995739.…”
Section: Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphasic taxonomy procedure indicated that this strain belonged to the genus Streptomyces and was closest to S. cinnamonensis [2]. Its 16S deoxyribonucleic acid (16S rDNA) sequence was deposited at NCBI GenBank with accession numbers KJ995739.…”
Section: Strainmentioning
confidence: 99%
“…To reveal the anti-infection reasons of this soil, a sample was collected in Xianjing Countryside in Zhuzhou County, China, and sixty-one actinomycete strains ZZ01 to ZZ061 were selectively isolated from this sample [1]. After chemical analysis were performed for discovering strains producing a series of secondary metabolites, the bioactive evaluation showed that thirteen strains had antimicrobial activities against Staphylococcus aureus, Escherichia coli and/or Candida albicans, and then the classification and identification of targeted seven strains indicated that they belonged to the genus Streptomyces [2]. Among them, Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%